High-activity vanadium-based catalytic system and olefin polymerization method

By using the use of all -halogen hydrocarbons as activists in the cymbal catalytic system, combined with the main catalyst and organic aluminum compounds to help the catalyst, to form a high -active cymbal catalytic system, solving the lack of high activity of the existing cymbal catalytic system and the cost of production costs High problems achieve the effect of improving aggregation activity and reducing production costs.

CN119371583APending Publication Date: 2025-01-28PETROCHINA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310912023.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing vanadium-based catalytic system is not very active in the production of ethylene-propylene rubber, and the active center of vanadium-based catalysts is prone to inactivate, resulting in high production costs and cumbersome product post-processing.

Method used

The all-halogen-representative hydrocarbon containing 1-5 carbon atoms is used as activists, combined with the main catalyst and organic aluminum compounds to help the catalyst, forming a high-active cymbal catalytic system, reducing the amount of catalytic agent and increasing aggregation activity.

Benefits of technology

It has improved the activity of the megal co -reaction of the meal, reducing the amount of main catalysts and catalysts, reducing production costs, and simplifying the post -processing process of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004355781720000081
    Figure BDA0004355781720000081
  • Figure BDA0004355781720000091
    Figure BDA0004355781720000091
  • Figure BDA0004355781720000131
    Figure BDA0004355781720000131
Patent Text Reader

Abstract

The invention provides a high-activity vanadium-based catalytic system and an olefin polymerization method, and belongs to the technical field of vanadium-based catalytic systems. The activating agent contained in the vanadium-based catalytic system provided by the invention is perhalogenated hydrocarbon containing 1-5 carbon atoms. When the vanadium-based catalytic system provided by the invention is applied to the synthesis of ethylene propylene rubber, the use amount of a main catalyst and a cocatalyst can be reduced while the activity of a copolymerization reaction for synthesizing the ethylene propylene rubber by olefin polymerization is improved, the residual amount of the catalyst in a product (dry glue) is reduced, the production cost is reduced, and the post-treatment of the product is easier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of vanadium-based catalyst systems, and in particular to a high-activity vanadium-based catalyst system and an olefin polymerization method. Background Art

[0002] Since the 1980s, EPDM has been a fast-growing product in synthetic rubber. Today, the catalytic systems used for the industrial production of EPDM mainly include Ziegler-Natta catalytic system, metallocene catalytic system, and post-metallocene catalytic system. However, due to the characteristics of mature technology and great process flexibility, the Ziegler-Natta vanadium-based catalytic system still accounts for a large proportion in the production of EPDM. This catalytic system usually uses vanadium trichloride (VOCl3), vanadium tetrachloride (VCl4), triacetylacetonate vanadium (V(acac)3) and the like as vanadium-based catalysts, alkyl aluminum halides as co-catalysts, and solution polymerization technology is used to produce EPDM. However, there are many shortcomings in the vanadium-based catalytic system, such as low activity and easy deactivation of the active center of the vanadium-based catalyst. If the amount of vanadium-based catalyst is increased, the content of vanadium and ash in the product will increase, which will not only affect the product performance but also make the post-processing of the rubber more complicated. In addition, it will also increase the cost of catalyst storage.

[0003] Many studies have found that adding an activator to the vanadium catalytic system can reactivate the deactivated vanadium center, thereby extending the life of the vanadium-based catalyst and increasing the activity of the vanadium-based catalyst. Therefore, adding a suitable activator to form a new vanadium-based catalytic system is one of the important methods to reduce production costs and increase polymerization activity. USP4181790 reported that the polymerization yield of the vanadium-based catalyst with 2,3,4,4-tetrachlorobutenoic acid ester as an activator is high, but the vanadium compound activated by it is very sensitive to air and water, and the actual application conditions are harsh; Japanese Patent 1973-71492 reported that the vanadium-based catalyst with anthraquinone oxides as an activator is highly active, but the compatibility is poor; CN85108910 reported that the catalyst activity system with trichlorofluoromethane and silicon tetrachloride as activators is highly active, but because silicon tetrachloride is corrosive and may cause pollution to the product. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a high-activity vanadium-based catalyst system and a method for olefin polymerization. The vanadium-based catalyst system provided by the present invention can reduce the amount of the main catalyst and the co-catalyst while improving the activity of the olefin polymerization reaction to synthesize ethylene-propylene rubber copolymerization, thereby reducing the production cost and making the post-processing of the product easier.

[0005] In order to achieve the above object, the present invention provides the following technical solution: a high-activity vanadium-based catalyst system, the vanadium-based catalyst system includes an activator; the activator is a perhalogenated hydrocarbon containing 1-5 carbon atoms.

[0006] Preferably, the activator is selected from at least one of trichlorofluoromethane, carbon tetrachloride, tetrachloroethylene, tetrafluoroethylene, hexafluoropropylene, hexachloropropylene, hexachlorobutadiene, and hexachlorocyclopentadiene.

[0007] Preferably, the vanadium-based catalytic system also includes a vanadium-based main catalyst; the general formula of the vanadium-based main catalyst is VO(OR)nClm, wherein the valence state of vanadium is positive pentavalent, OR is an alkoxy group, n is 1, 2, or 3, m is 0, 1, or 2, and m+n=3.

[0008] Further preferably, the alkoxy group in the vanadium-based main catalyst structure is at least one of methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentoxy, n-hexoxy, and cyclohexyloxy.

[0009] Preferably, the vanadium-based catalyst system further comprises a co-catalyst; the co-catalyst is an organic aluminum compound.

[0010] Further preferably, the molar ratio of aluminum atoms in the co-catalyst to vanadium in the vanadium-based main catalyst is (1-100):1; the molar ratio of the activator to vanadium in the vanadium-based main catalyst is (5-80):1.

[0011] The present invention also provides a method for olefin polymerization, wherein ethylene, propylene and a molecular weight regulator are copolymerized under the vanadium-based catalyst system described in the above technical solution; or, ethylene, propylene, a diene and a molecular weight regulator are copolymerized under the vanadium-based catalyst system described in the above technical solution.

[0012] Preferably, the molecular weight regulator is hydrogen.

[0013] Preferably, the diene is one of ethylidene norbornene, dicyclopentadiene and 1,4-hexadiene.

[0014] Preferably, the copolymerization reaction temperature is 0-75° C.; the copolymerization reaction time is 10-180 min; and the copolymerization reaction pressure is 0.1-1.0 MPa.

[0015] Beneficial technical effects: The activator contained in the vanadium-based catalyst system provided by the present invention is a perhalogenated hydrocarbon containing 1 to 5 carbon atoms. The vanadium-based catalyst system provided by the present invention is applied to the synthesis of ethylene-propylene rubber, which can reduce the amount of the main catalyst and the co-catalyst while improving the activity of the synthetic ethylene-propylene rubber copolymerization reaction, reduce the amount of catalyst residue in the product (dry rubber), reduce production costs, and make the post-processing of the product easier. DETAILED DESCRIPTION

[0016] The invention provides a high-activity vanadium-based catalyst system, which comprises an activator; the activator is a perhalogenated hydrocarbon containing 1 to 5 carbon atoms.

[0017] In the present invention, the activator is selected from at least one of trichlorofluoromethane, carbon tetrachloride, tetrachloroethylene, tetrafluoroethylene, hexafluoropropylene, hexachloropropylene, hexachlorobutadiene, and hexachlorocyclopentadiene.

[0018] In the present invention, the vanadium-based catalytic system also includes a vanadium-based main catalyst; the general formula of the vanadium-based main catalyst is VO(OR)nClm, wherein the valence state of vanadium is positive pentavalent, OR is an alkoxy group, n is 1, 2, or 3, m is 0, 1, or 2, and m+n=3.

[0019] In the present invention, the alkoxy group in the vanadium-based main catalyst structure is preferably at least one of methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentoxy, n-hexoxy, and cyclohexyloxy.

[0020] In the present invention, the vanadium-based catalyst system also includes a co-catalyst; the co-catalyst is an organic aluminum compound, preferably an alkyl aluminum chloride, more preferably at least one of dimethylaluminum chloride, diethylaluminum chloride, di-n-butylaluminum chloride, diisobutylaluminum chloride, methylaluminum dichloride, ethylaluminum dichloride, n-butylaluminum dichloride, isobutylaluminum dichloride, sesquimethylaluminum chloride, sesquiethylaluminum chloride, sesqui-n-butylaluminum chloride and sesqui-isobutylaluminum chloride, and most preferably sesquiethylaluminum chloride.

[0021] In the present invention, the molar ratio of aluminum atoms in the co-catalyst to vanadium in the vanadium-based main catalyst is preferably (1-100):1, more preferably (20-60):1; the molar ratio of the activator to vanadium in the vanadium-based main catalyst is preferably (5-80):1, more preferably (5-20):1, and most preferably (5-10):1.

[0022] The present invention also provides a method for olefin polymerization, wherein ethylene, propylene and a molecular weight regulator are copolymerized under the vanadium-based catalyst system described in the above technical solution; or, ethylene, propylene, a diene and a molecular weight regulator are copolymerized under the vanadium-based catalyst system described in the above technical solution.

[0023] In the present invention, the molecular weight regulator is preferably hydrogen; the molar ratio of hydrogen in the mixed gas of ethylene, propylene and hydrogen is preferably 1% to 3%.

[0024] In the present invention, the molar ratio of propylene to ethylene in the ethylene-propylene mixed gas is preferably (1-5):1.

[0025] In the present invention, the diene is preferably one of ethylidene norbornene (ENB), dicyclopentadiene and 1,4-hexadiene.

[0026] In the present invention, the copolymerization reaction further comprises using a polymerization solvent, and the polymerization solvent is preferably an aliphatic alkane or a cycloalkane, more preferably hexane or cyclohexane, and most preferably ethane.

[0027] In the present invention, the copolymerization reaction further comprises using a terminator, and the terminator is preferably ethanol.

[0028] In the present invention, the copolymerization reaction temperature is preferably 0 to 75° C.; the copolymerization reaction time is preferably 10 to 180 min; and the copolymerization reaction pressure is preferably 0.1 to 1.0 MPa.

[0029] In the present invention, when ethylene, propylene and a molecular weight regulator are copolymerized under the vanadium-based catalyst system described in the above technical solution, the copolymerization reaction is specifically performed as follows:

[0030] The reactor is treated to be anhydrous and oxygen-free, and then a solvent equivalent to 40-70% of the reactor volume is added to the reactor, and then a raw gas is introduced into the reactor. In the present invention, the raw gas is prepared according to a molar ratio of ethylene:propylene:hydrogen=1:(4-5):(0.01-0.03), and then a vanadium-based main catalyst, a co-catalyst and an activator are added, wherein the addition amount of the vanadium-based main catalyst is 0.02-0.1mmol / 100mL of solvent, the addition amount of the co-catalyst is 0.02-10mmol / 100mL of solvent, and the addition amount of the activator is 0.02-8mmol / 100mL of solvent. During the reaction, the polymerization reaction pressure is controlled to be constant at 0.1-1.0MPa by a raw gas adding valve. After 30-120 minutes of polymerization, ethanol is added to terminate the reaction.

[0031] In the present invention, the reactor used in the polymerization reaction is a jacketed reactor, and the jacket can be used to pass cooling medium to control the reaction temperature.

[0032] In the present invention, when ethylene, propylene, diene and molecular weight regulator are copolymerized under the vanadium-based catalyst system described in the above technical solution, the copolymerization reaction is specifically performed as follows:

[0033] The reactor is treated to be anhydrous and oxygen-free, and then a solvent equivalent to 40-70% of the reactor volume is added to the reactor, and then a raw gas is introduced into the reactor. In the present invention, the raw gas is prepared according to a molar ratio of ethylene:propylene:hydrogen=1:(4-5):(0.01-0.03), and then a vanadium-based main catalyst, a co-catalyst, an activator and a diene are added, wherein the addition amount of the vanadium-based main catalyst is 0.02-0.1mmol / 100mL of the solvent, the addition amount of the co-catalyst is 0.02-10mmol / 100mL of the solvent, the addition amount of the activator is 0.02-8mmol / 100mL of the solvent, and the addition amount of the diene is 2-8mL / 100mL of the solvent. During the reaction, the polymerization reaction pressure is controlled to be constant at 0.1-1.0MPa by a raw gas adding valve. After 30-120 minutes of polymerization, ethanol is added to terminate the reaction.

[0034] In the present invention, the reactor used in the polymerization reaction is a jacketed reactor, and the jacket can be used to pass cooling medium to control the reaction temperature.

[0035] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0036] The activity of the catalyst is calculated based on the mass of dry polymer produced per mole of vanadium-based main catalyst, in units of gpolymer. (mol -1 of V).

[0037] According to SH / T 1751-2005, the ethylene monomer and propylene monomer contents of EPDM rubber were determined by Fourier transform infrared spectrometer (FTIR).

[0038] According to GB / T 21864-2008, the average molecular weight and molecular weight distribution of the copolymer were determined by high performance size exclusion chromatography (HPSEC).

[0039] Example 1

[0040] The polymerization reaction was carried out in a 2L stainless steel jacketed polymerization kettle. First, the polymerization kettle was treated with anhydrous and oxygen-free treatment for 1 hour. Then, 1L of dry hexane (water content ≤ 10ppm) was added thereto. Then, a raw material gas prepared according to a molar ratio of ethylene, propylene, and hydrogen of 1:4.5:0.015 was introduced. Then, 0.3mmol of vanadium-based main catalyst dichloroethoxyvanadium (VO(OEt)Cl2, VX), 6mmol of co-catalyst sesquiethylaluminum chloride (AQ), and 1.5mmol of activator hexachloropropylene (HCP) were added. The polymerization reaction was carried out at room temperature. During the reaction, the polymerization reaction pressure was controlled to be constant at 0.5MPa by a raw material gas adding valve. The polymerization reaction time was 30 minutes. After the polymerization was completed, the glue solution was discharged from the bottom pipe of the polymerization kettle. After being terminated with ethanol, a large amount of ethanol was used to precipitate the ethylene-propylene binary copolymer. The precipitated ethylene-propylene copolymer was dried in a vacuum oven to obtain 36.32g of dry glue.

[0041] The catalyst activity in this example was calculated to be 1.21×10 5 g polymer.(mol -1 The weight average relative molecular weight of the obtained dry rubber was about 70,000, the relative molecular weight distribution was 2.4, the ethylene content was 51.6%, and the propylene content was 48.4%.

[0042] Compared with Comparative Example 1, the catalytic activity of the catalyst system increased by 14.2%.

[0043] Compared with Comparative Example 6, the catalytic activity of the catalyst system increased by 42.4%.

[0044] Example 2

[0045] The same as Example 1, except that the amount of AQ added was changed to 12 mmol, and 35.09 g of dry gum was obtained.

[0046] The calculated catalyst activity in this example is 1.17×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 90,000, the relative molecular weight distribution was 2.7, the ethylene content was 52.5%, and the propylene content was 47.5%.

[0047] Compared with Comparative Example 2, the catalytic activity of the catalyst system was increased by 33.0%.

[0048] Compared with Comparative Example 6, the catalytic activity of the catalyst system is increased by 37.6%.

[0049] Example 3

[0050] The same as Example 1, except that the amount of AQ added was changed to 18 mmol, and 41.75 g of dry gum was obtained.

[0051] The calculated catalyst activity in this example is 1.39×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 110,000, the relative molecular weight distribution was 3.1, the ethylene content was 54.3%, and the propylene content was 45.7%.

[0052] Compared with Comparative Example 3, the catalytic activity of the catalyst system increased by 78.2%.

[0053] Compared with Comparative Example 6, the catalytic activity of the catalyst system increased by 63.5%.

[0054] Example 4

[0055] The same as Example 1, except that the amount of AQ added was changed to 24 mmol, and 38.89 g of dry gum was obtained.

[0056] The catalyst activity in this example is calculated to be 1.30×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 100,000, the relative molecular weight distribution was 2.8, the ethylene content was 51.4%, and the propylene content was 48.6%.

[0057] Compared with Comparative Example 4, the catalytic activity of the catalyst system increased by 42.9%.

[0058] Compared with Comparative Example 6, the catalytic activity of the catalyst system increased by 52.9%.

[0059] Example 5

[0060] The same as Example 2, except that the vanadium-based main catalyst and the activator were changed. 0.3 mmol of the vanadium-based main catalyst diethoxyvanadium chloride VO(OEt)2Cl (abbreviated as VY) was added, and 1.5 mmol of the activator HCCP was added to obtain 35.01 g of dry rubber.

[0061] The calculated catalyst activity in this example is 1.17×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 100,000, the relative molecular weight distribution was 2.1, the ethylene content was 53.8%, and the propylene content was 46.2%.

[0062] Compared with Comparative Example 6, the catalytic activity of the catalyst system is increased by 37.6%.

[0063] Example 6

[0064] The same as Example 2, except that the alkyl aluminum halide co-catalyst and the activator were changed, 12 mmol of diethylaluminum chloride (DEAC) and 1.5 mmol of activator HCCP were added, and 36.31 g of dry rubber was obtained.

[0065] The catalyst activity in this example was calculated to be 1.21×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 100,000, the relative molecular weight distribution was 2.3, the ethylene content was 53.1%, and the propylene content was 46.9%.

[0066] Compared with Comparative Example 6, the catalytic activity of the catalyst system increased by 42.4%.

[0067] Example 7

[0068] The same as Example 2, except that the alkyl aluminum halide co-catalyst and the activator were changed, 12 mmol of dimethyl aluminum chloride (DMAC) and 1.5 mmol of activator HCCP were added, and 34.66 g of dry rubber was obtained.

[0069] The catalyst activity in this example is calculated to be 1.16×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 100,000, the relative molecular weight distribution was 2.1, the ethylene content was 51.9%, and the propylene content was 48.1%.

[0070] Compared with Comparative Example 6, the catalytic activity of the catalyst system is increased by 36.5%.

[0071] Comparative Example 1

[0072] Same as Example 1, except that the amount of activator was changed to 0.75 mmol, and 32.08 g of dry gel was obtained. The catalyst activity in this example was calculated to be 1.06×10 5 g polymer.(mol -1 The weight average relative molecular weight of the obtained dry rubber was about 150,000, the relative molecular weight distribution was 2.9, the ethylene content was 51.7%, and the propylene content was 48.3%.

[0073] Comparative Example 2

[0074] Same as Example 2, except that the amount of activator was changed to 0.75 mmol, and 26.32 g of dry gel was obtained. The catalyst activity in this example was calculated to be 0.88×10 5 g polymer.(mol -1of V). The weight average relative molecular weight of the obtained dry rubber was about 120,000, the relative molecular weight distribution was 2.7, the ethylene content was 54.9%, and the propylene content was 45.1%.

[0075] Comparative Example 3

[0076] Same as Example 3, except that the amount of activator was changed to 0.75 mmol, and 23.47 g of dry gel was obtained. The catalyst activity in this example was calculated to be 0.78×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 110,000, the relative molecular weight distribution was 2.8, the ethylene content was 54.8%, and the propylene content was 45.2%.

[0077] Comparative Example 4

[0078] Same as Example 4, except that the amount of activator was changed to 0.75 mmol, and 27.58 g of dry gel was obtained. The catalyst activity in this example was calculated to be 0.91×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 100,000, the relative molecular weight distribution was 28, the ethylene content was 57.9%, and the propylene content was 42.1%.

[0079] Comparative Example 5

[0080] The same as Example 1, except that the amount of the co-catalyst was changed to 3 mmol, and the amount of the activator was changed to 0.75 mmol, to obtain 36.04 g of dry glue. The catalyst activity in this example was calculated to be 1.20×10 5 g polymer.(mol -1 The weight average relative molecular weight of the obtained dry rubber was about 110,000, the relative molecular weight distribution was 2.3, the ethylene content was 54.8%, and the propylene content was 45.2%.

[0081] Comparative Example 6

[0082] The same as Example 1, except that no activator was added, and 25.50 g of dry glue was obtained. The catalyst activity in this example was calculated to be 0.85×10 5 g polymer.(mol -1 The weight average relative molecular weight of the obtained dry rubber was about 260,000, the relative molecular weight distribution was 2.2, the ethylene content was 60.9%, and the propylene content was 39.1%.

[0083] The relevant parameters such as yield, catalytic activity, weight average molecular weight, molecular weight distribution, ethylene content, propylene content, etc. in Examples 1-7 and Comparative Examples 1-6 are shown in Table 1.

[0084] Table 1

[0085]

[0086]

[0087] Example 8

[0088] The polymerization reaction was carried out in a stainless steel jacketed polymerization kettle with a volume of 2L. First, the polymerization kettle was treated with anhydrous and oxygen-free treatment for 1 hour. Then, 1L of dry hexane (water content ≤10ppm) was added thereto. Then, a raw material gas prepared according to a molar ratio of ethylene, propylene, and hydrogen of 1:4.5:0.015 was introduced. Then, 0.3mmol of vanadium-based main catalyst dichloroethoxyvanadium (VO(OEt)Cl2, VX), 6mmol of co-catalyst sesquiethylaluminum chloride (AQ), 1.5mmol of activator hexachloropropylene (HCP) were added. Finally, 35mL of ENB was added. The polymerization reaction was carried out at room temperature. During the reaction, the polymerization reaction pressure was controlled to be constant at 0.5MPa by a raw material gas adding valve. The polymerization reaction time was 30 minutes. After the polymerization was completed, the glue solution was discharged from the bottom pipe of the polymerization kettle. After being terminated with ethanol, a large amount of ethanol was used to precipitate the ethylene-propylene terpolymer. The precipitated ethylene-propylene copolymer was dried in a vacuum oven to obtain 40.55g of dry glue.

[0089] The catalyst activity in this example is calculated to be 1.35×10 5 g polymer.(mol -1 of V), the weight average relative molecular weight of the obtained dry rubber was about 330,000, the relative molecular weight distribution was 4.7, the ethylene content was 50.6%, the propylene content was 41.8%, and the ENB content was 7.6%.

[0090] Compared with Comparative Example 7, the catalytic activity of the catalyst system is increased by 18.4%.

[0091] Compared with Comparative Example 12, the catalytic activity of the catalyst system was increased by 92.9%.

[0092] Example 9

[0093] The same as Example 8, except that the amount of AQ added was changed to 12 mmol, and 48.82 g of dry gum was obtained.

[0094] The catalyst activity in this example is calculated to be 1.63×10 5 g polymer.(mol -1of V). The weight average relative molecular weight of the obtained dry rubber was about 330,000, the relative molecular weight distribution was 4.3, the ethylene content was 52.3%, the propylene content was 39.3%, and the ENB content was 8.4%.

[0095] Compared with Comparative Example 8, the catalytic activity of the catalyst system increased by 55.2%.

[0096] Compared with Comparative Example 12, the catalytic activity of the catalyst system is increased by 132.9%.

[0097] Example 10

[0098] The same as Example 8, except that the amount of AQ added was changed to 18 mmol, and 42.43 g of dry gum was obtained.

[0099] The catalyst activity in this example was calculated to be 1.41×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 340,000, the relative molecular weight distribution was 4.6, the ethylene content was 51.6%, the propylene content was 39.2%, and the ENB content was 9.2%.

[0100] Compared with Comparative Example 9, the catalytic activity of the catalyst system was increased by 43.9%.

[0101] Compared with Comparative Example 12, the catalytic activity of the catalyst system increased by 101.4%.

[0102] Embodiment 11

[0103] The same as Example 8, except that the amount of AQ added was changed to 24 mmol, and 40.76 g of dry gum was obtained.

[0104] The calculated catalyst activity in this example is 1.36×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 350,000, the relative molecular weight distribution was 4.2, the ethylene content was 50.4%, the propylene content was 39.4%, and the ENB content was 10.1%.

[0105] Compared with Comparative Example 10, the catalytic activity of the catalyst system is increased by 49.5%.

[0106] Compared with Comparative Example 12, the catalytic activity of the catalyst system increased by 94.3%.

[0107] Example 12

[0108] Same as Example 9, except that the vanadium-based main catalyst and activator were changed. 0.3 mmol of vanadium-based main catalyst diethoxyvanadium chloride VO(OEt)2Cl (abbreviated as VY) was added, and 1.5 mmol of activator HCCP was added to obtain 41.82 g of dry rubber.

[0109] The calculated catalyst activity in this example is 1.39×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 350,000, the relative molecular weight distribution was 4.2, the ethylene content was 52.8%, the propylene content was 38.6%, and the ENB content was 8.6%.

[0110] Compared with Comparative Example 12, the catalytic activity of the catalyst system was increased by 98.6%.

[0111] Embodiment 13

[0112] The same as Example 9, except that the alkyl aluminum halide co-catalyst and the activator were changed, 12 mmol of diethylaluminum chloride (DEAC) and 1.5 mmol of activator HCCP were added, and 43.45 g of dry rubber was obtained.

[0113] The catalyst activity in this example is calculated to be 1.45×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 350,000, the relative molecular weight distribution was 4.4, the ethylene content was 53.1%, the propylene content was 38.2%, and the ENB content was 8.7%.

[0114] Compared with Comparative Example 12, the catalytic activity of the catalyst system increased by 107.1%.

[0115] Embodiment 14

[0116] The same as Example 9, except that the alkylaluminum halide co-catalyst and the activator were changed, 12 mmol of dimethylaluminum chloride (DMAC) and 1.5 mmol of activator HCCP were added, and 42.86 g of dry gum was obtained.

[0117] The catalyst activity in this example is calculated to be 1.43×10 5 g polymer.(mol -1 The weight average relative molecular weight of the obtained dry rubber was about 330,000, the relative molecular weight distribution was 4.5, the ethylene content was 52.7%, the propylene content was 38.3%, and the ENB content was 9.0%.

[0118] Compared with Comparative Example 12, the catalytic activity of the catalyst system increased by 104.3%.

[0119] Comparative Example 7

[0120] Same as Example 8, except that the amount of activator was changed to 0.75 mmol, and 34.28 g of dry gel was obtained. The catalyst activity in this example was calculated to be 1.14×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 320,000, the relative molecular weight distribution was 4.8, the ethylene content was 52.7%, the propylene content was 40.2%, and the ENB content was 7.1%.

[0121] Comparative Example 8

[0122] Same as Example 9, except that the amount of activator was changed to 0.75 mmol, and 31.63 g of dry gel was obtained. The catalyst activity in this example was calculated to be 1.05×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 330,000, the relative molecular weight distribution was 4.9, the ethylene content was 53.9%, the propylene content was 38.2%, and the ENB content was 7.9%.

[0123] Comparative Example 9

[0124] Same as Example 10, except that the amount of activator was changed to 0.75 mmol, and 29.31 g of dry gel was obtained. The catalyst activity in this example was calculated to be 0.98×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 320,000, the relative molecular weight distribution was 5.1, the ethylene content was 53.8%, the propylene content was 38.1%, and the ENB content was 8.1%.

[0125] Comparative Example 10

[0126] Same as Example 11, except that the amount of activator was changed to 0.75 mmol, and 27.16 g of dry gel was obtained. The catalyst activity in this example was calculated to be 0.91×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 330,000, the relative molecular weight distribution was 5.2, the ethylene content was 52.9%, the propylene content was 38.7%, and the ENB content was 8.4%.

[0127] Comparative Example 11

[0128] Same as Example 8, except that the amount of the co-catalyst was changed to 3 mmol, and the amount of the activator was changed to 0.75 mmol, and 37.23 g of dry gum was obtained. The catalyst activity in this example was calculated to be 1.24×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 320,000, the relative molecular weight distribution was 4.9, the ethylene content was 51.8%, the propylene content was 40.6%, and the ENB content was 7.6%.

[0129] Comparative Example 12

[0130] The same as Example 8, except that no activator was added, and 20.88 g of dry glue was obtained. The catalyst activity in this example was calculated to be 0.70×10 5 g polymer.(mol -1 of V). The weight average relative molecular weight of the obtained dry rubber was about 420,000, the relative molecular weight distribution was 4.7, the ethylene content was 54.1%, the propylene content was 35.7%, and the ENB content was 10.2%.

[0131] The relevant parameters such as yield, catalytic activity, weight average molecular weight, molecular weight distribution, ethylene content, propylene content, etc. in Examples 8-14 and Comparative Examples 7-12 are shown in Table 2.

[0132] Table 2

[0133]

[0134]

[0135] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A highly active vanadium-based catalyst system, characterized in that: The vanadium-based catalyst system comprises an activator; the activator is a perhalogenated hydrocarbon containing 1 to 5 carbon atoms.

2. The vanadium-based catalyst system according to claim 1, characterized in that The activator is selected from at least one of trichlorofluoromethane, carbon tetrachloride, tetrachloroethylene, tetrafluoroethylene, hexafluoropropylene, hexachloropropylene, hexachlorobutadiene, and hexachlorocyclopentadiene.

3. The vanadium-based catalyst system according to claim 1, characterized in that The vanadium-based catalytic system also includes a vanadium-based main catalyst; the general formula of the vanadium-based main catalyst is VO(OR)nClm, wherein the valence state of vanadium is positive pentavalent, OR is an alkoxy group, n is 1, 2, or 3, m is 0, 1, or 2, and m+n=3.

4. The vanadium-based catalytic system according to claim 3, characterized in that The alkoxy group in the vanadium-based main catalyst structure is at least one of methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentoxy, n-hexoxy, and cyclohexyloxy.

5. The vanadium-based catalyst system according to claim 1, characterized in that: The vanadium-based catalyst system also includes a co-catalyst; the co-catalyst is an organic aluminum compound.

6. The vanadium-based catalytic system according to claim 5, characterized in that: The molar ratio of the aluminum atoms in the co-catalyst to the vanadium in the vanadium-based main catalyst is (1-100):1; the molar ratio of the activator to the vanadium in the vanadium-based main catalyst is (5-80):

1.

7. A method for olefin polymerization, characterized in that: The method comprises the following steps of: copolymerizing ethylene, propylene and a molecular weight regulator under the vanadium-based catalyst system of claim 1; or copolymerizing ethylene, propylene, a diene and a molecular weight regulator under the vanadium-based catalyst system of claim 1.

8. The method according to claim 7, characterized in that The molecular weight regulator is hydrogen.

9. The method according to claim 7, characterized in that: The diene is one of ethylidene norbornene, dicyclopentadiene and 1,4-hexadiene.

10. The method according to claim 7, characterized in that The copolymerization reaction temperature is 0-75°C; the copolymerization reaction time is 10-180 min; and the copolymerization reaction pressure is 0.1-1.0 MPa.

Citation Information

Patent Citations

  • Polymerization catalyst, production and use

    CN85108910A

  • Vanadium catalysis system for combined polymerization of ethylene, propylene, and diolefin, and application

    CN101092466A

  • Olefin monomer copolymerization method and application thereof

    CN114213564A

  • Process for the preparation of a copolymer of ethylene

    US20140249282A1